2019
DOI: 10.1161/strokeaha.119.025350
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Risk Factors of Cerebral Ischemic Events in Patients With Atrial Fibrillation Treated With Non–Vitamin K Antagonist Oral Anticoagulants for Stroke Prevention

Abstract: Background and Purpose— Despite treatment with oral anticoagulants, patients with nonvalvular atrial fibrillation (AF) may experience ischemic cerebrovascular events. The aims of this case-control study in patients with AF were to identify the pathogenesis of and the risk factors for cerebrovascular ischemic events occurring during non–vitamin K antagonist oral anticoagulants (NOACs) therapy for stroke prevention. Methods— Cases were consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 23 publications
(18 reference statements)
5
54
0
1
Order By: Relevance
“…This may result in a higher risk of retinal vascular occlusion with lower efficacy. Similarly, off-label low dose of NOAC was associated with increased risk of cerebral ischemic events 33 , and these tendencies of ischemic event need further investigation along with the gender difference.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in a higher risk of retinal vascular occlusion with lower efficacy. Similarly, off-label low dose of NOAC was associated with increased risk of cerebral ischemic events 33 , and these tendencies of ischemic event need further investigation along with the gender difference.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the RENo study examining NOAC-treated AF patients with an acute ischemic stroke, about 30% of patients had a stroke due to causes other than cardio-embolism (e.g. small vessel disease) (Paciaroni et al, 2019).…”
Section: Mortalitymentioning
confidence: 99%
“…Of fundamental importance for the organization of care for patients with ACA have works in which it was found that neuroimaging and primary neuroprotective therapy should begin within the "therapeutic window" and that their implementation during this period reduces mortality and disability due to stroke [1,5,8]. At the same time, a number of authors point to the leading role of the nature, location and extent of brain damage [11].…”
Section: Discussionmentioning
confidence: 99%